Effect of organic fertilizer " Orgomin" and seaweed extract " Amino Food " on leaf content of chlorophyll and fruit quality of citrus cultivar "Valencia" - شعبو, نجلاء; جرجس مخول , (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out in the village of Fdeo in Lattakia Governorate during the year (2022) on citrus trees of the "Valencia" variety, 15 years old, grafted on Citrus aurantium rootstock. The experiment was carried out with 9 treatments, each treatment with three replications. The aim of the research was to study the effect of foliar feeding with the organic fertilizer "ergomin" and seaweed extract "Amino Food" on improving the leaf content of chlorophyll and fruit quality of the orange variety "Valencia". The results showed the following: - The treatment (Orgomin 2 cm3/liter + Amino Food 2 cm3/liter) gave the highest leaf content of chlorophyll a and b and total chlorophyll (0.749 mg/g, 0.478 mg/g, and 1.227 mg/g) respectively. The results of the statistical analysis showed the superiority of this treatment over all other treatments. In terms of fruit quality, the results showed that the treatment (Orgomin 2 cm3/liter + Amin Food 2 cm3/liter) was superior in the average weight of the fruit (284.50g) and the fruit juice content of total dissolved solids with a value of (12.33%), and the treatment (Orgomin 1.5 cm3/liter + Amino Food) was superior. 1 cm3/liter) in the juice content of total sugars with a value of (9.99%). As for the acidity of the juice, spraying with (Orgomin 2 cm3/liter + Amino food 1 cm3/liter) resulted in a decrease in total acidity (0.359%) compared to the control that achieved the highest increase in total acidity with a value of (1.127%). Accordingly, foliar feeding with biofertilizer and seaweed extract can be used to improve the chlorophyll content of the leaves and improve the quality of the fruits.